2017
DOI: 10.3892/ol.2017.6367
|View full text |Cite
|
Sign up to set email alerts
|

Association between human papillomavirus and prostate cancer: A meta-analysis

Abstract: Abstract. Observational studies have suggested an association between human papillomavirus (HPV) infection and the risk of prostate cancer (PCa). However, the association between HPV infection and the risk of PCa remains unclear. The aim of the present meta-analysis study was to investigate whether HPV serves a role in increasing the risk of PCa. Relevant previous studies up to May 2015 were searched in PubMed, Web of Science, Cochrane library, Chinese National Knowledge Infrastructure, China Wan Fang database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 86 publications
2
22
0
Order By: Relevance
“…The detected high frequency of high-risk HPVs in the investigated Bulgarian prostatic tumor-specific specimens with molecular alterations is in accordance with the reported data in Europe and confirms the hypothesis for the participation of HPV as an inflammatory cofactor in the complex etiology of PCa [40]. The prevalence of HPVs from the subgroup with highest oncogenic potential provides another evidence for the role of the viral component in the initiation and even progression of PCa.…”
Section: Discussionsupporting
confidence: 89%
“…The detected high frequency of high-risk HPVs in the investigated Bulgarian prostatic tumor-specific specimens with molecular alterations is in accordance with the reported data in Europe and confirms the hypothesis for the participation of HPV as an inflammatory cofactor in the complex etiology of PCa [40]. The prevalence of HPVs from the subgroup with highest oncogenic potential provides another evidence for the role of the viral component in the initiation and even progression of PCa.…”
Section: Discussionsupporting
confidence: 89%
“…Chronic prostate inflammation (that could be induced by a viral infection) is thought to increase the risk of prostate cancer (436), and a link between prostate cancer, sexual activity and sexually-transmitted infection was reported in some studies (306). However, despite years of investigations on HPV (3,35,301,675,756,760), KSHV, EBV, BK virus, CMV (3, 301), and the "rumor" virus Xenotropic murine leukemia related virus (XMRV) (531) through serology testing or prostate tissue analysis by PCR, in situ hybridization or immunohistochemistry, there is no compelling evidence for a viral etiology of prostate cancer. Nevertheless, a few studies suggested that KSHV and HPV may represent a risk factor for prostate cancer aggressiveness (239,494,756).…”
Section: Prostate Cancermentioning
confidence: 99%
“…The strong association was proven only for human papilloma virus (HPV) and penile cancer risk [ 10 ]. However, more and more research shows a possible link between viral infections and urothelial cancer [ 11 , 12 , 13 , 14 , 15 ], prostate cancer [ 15 , 16 , 17 ] or testicular cancer [ 18 , 19 ]. Furthermore, the evidence behind the role of latent viral infections in carcinogenesis of RCC is growing.…”
Section: Introductionmentioning
confidence: 99%